Perbedaan Efektivitas Pemberian Kompres Hangat Dengan Aromaterapi Lavender Terhadap Penurunan Tingkat Dismenore Pada Remaja Putri - Yulia Pranata; Wiwin Nur Fitriani; Nur Handayani (Indonesian Journal of Midwifery Scientific, 2026)
Background: Dysmenorrhea is a disturbance of discomfort or pain during menstruation that causes disruption of daily activities. Dysmenorrhea is caused by an increase in the hormone prostaglandins that cause contact of the uterine muscles. Warm compresses and lavender aromatherapy are non-pharmacological methods that are often used to reduce dysmenorrhea pain in adolescent girls. Research shows that both therapies can help relieve pain by improving blood circulation and providing a relaxing effect. Objective: To determine the reduction of dysmenorrhea pain with the administration of warm compresses and lavender aromatherapy. Research Methodology: This study was conducted with a Quassy Experiment with a One Group Pretest and Posttest design. The sample size in this study was 78 respondents who suffered from dysmenorrhea on the first day and the second day with the Purposive Sampling Method. Data analysis was carried out univariate and bivariate. Results: The pain level after treatment between the Warm Compress and Lavender Aromatherapy groups did not differ significantly Because p-value = 0.491, so H₀ was accepted. Conclusion: The level of pain after treatment between the Warm Compress and Lavender Aromatherapy groups was not different in the adolescent girls of SMK Kesehatan Letris Indonesia 2 Suggestion: It is expected to increase knowledge about reproductive health and its problems and be able to determine the correct and safe attitude to problems in adolescents. Keywords: Dysmenorrhea Level, Warm Compress, Lavender Aromatherapy.